Museum Retribution and Hybrid Organization: A Sustainable Funding Model for Cultural Heritage Preservation in Jakarta - Selvi; Milaty Fatwa Indah; Maryatul Kibtiah; Anita Maulina (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
Museum retribution plays an important role in supporting the preservation of cultural heritage in Jakarta; however, its contribution remains insufficient to finance museum operations, conservation activities, and educational programs. This study aims to analyze the existing museum funding system using Soft Systems Methodology (SSM) to identify institutional problems, stakeholder roles, and fiscal constraints, and to develop a sustainable hybrid organization-based management model. A qualitative approach was employed through interviews with museum managers, field observations, and document analysis. Data were analyzed using the seven stages of SSM, including rich picture development, CATWOE analysis, conceptual modelling, and comparison between the conceptual model and the existing system. The findings reveal that the primary challenge lies not in the lack of revenue potential but in the bureaucratic management system, which limits managerial autonomy and prevents museums from utilizing their own retribution revenue. The SSM analysis further demonstrates that a tourism-oriented regional-owned enterprise (BUMD) operating as a hybrid organization provides a feasible institutional alternative by diversifying funding sources, strengthening stakeholder collaboration, and improving financial sustainability while preserving the museum's public mission. These findings contribute to the development of a sustainable museum funding model and offer policy recommendations for strengthening cultural heritage governance in Jakarta.